Sensitive Detection of Peptide–Minicircle DNA Interactions by Surface Plasmon Resonance - Gaspar, Vítor Manuel Abreu (2018)
Minicircle DNA (mcDNA) is recently becoming an exciting source of genetic material for therapeutic purposes due to its exceptional biocompatibility and efficiency over typical DNA. However, its widespread use is yet restrained because of the absence of an efficient technology that allows its purification. Here, the precise conditions of mcDNA interaction with novel arginine-arginine dipeptide ligands were explored to promote binding and recovery of these biopharmaceuticals. Such interactions were investigated by taking advantage of a highly sensitive method based on surface plasmon resonance (SPR) to screen, in real-time, for ligand-coupled biomolecules, while preserving mcDNA integrity. Through this analytic approach, we detected dynamic binding responses that are dependent on buffer type, mcDNA electrokinetic potential, and temperature conditions. Remarkably, the results obtained revealed that the ligands possess high affinity to mcDNA molecules under low salt buffers, and low affinity in the presence of salt, suggesting that electrostatic interactions mainly govern ligand–analyte coupling. These findings provide important insights for an active manipulation of parameters that promote mcDNA recovery and purification. Above all, this study showed the crucial importance of SPR for future screening of other ligands that, like the one described herein, can be used to design mcDNA recovery platforms which will have significant impact in biopharmaceutical-based therapeutics.